Status and Corporate Illegality: Illegal Loan Recovery Practices of Commercial Banks in India - Krishnan, Rekha; Kozhikode, Rajiv Krishnan (Academy of Management Journal, 2015)
Why might high-status organizations, presumably secure in their positions, resort to illegality? This study considers the possibility that status theory might have overestimated the relative security of high-status organizations. We examine our theory that an inability to meet associates’ expectations about quality might be the source of insecurity, using data on the illegal loan recovery practices employed by commercial banks in India between 2005 and 2009. High-status banks were found to be particularly likely to engage in illegal recovery practices. This was especially true when a high-status bank had experienced a decline in its financial asset quality or had fallen behind the financial asset quality of its peers. However, when a bank’s business partners placed greater emphasis on corporate social responsibility (CSR), it minimized a bank’s tendency to resort to illegal loan recovery practices.